Current applications and future prospects of nanomaterials in tumor therapy - Huang Y; Fan CQ; Dong H; Wang SM; Yang XC; Yang SM (International Journal of Nanomedicine, 2017)
Yu Huang,1 Chao-Qiang Fan,1 Hui Dong,1 Su-Min Wang,1 Xiao-Chao Yang,2 Shi-Ming Yang1 1Department of Gastroenterology, Xinqiao Hospital, Third Military Medical University, Chongqing, People’s Republic of China; 2Department of Biomedical Materials Science, School of Biomedical Engineering, Third Military Medical University, Chongqing, People’s Republic of China Abstract: Tumors are one of the most serious human diseases and cause numerous global deaths per year. In spite of many strategies applied in tumor therapy, such as radiation therapy, chemotherapy, surgery, and a combination of these treatments, tumors are still the foremost killer worldwide among human diseases, due to their specific limitations, such as multidrug resistance and side effects. Therefore, it is urgent and necessary to develop new strategies for tumor therapy. Recently, the fast development of nanoscience has paved the way for designing new strategies to treat tumors. Nanomaterials have shown great potential in tumor therapy, due to their unique properties, including passive targeting, hyperthermia effects, and tumor-specific inhibition. This review summarizes the recent progress using the innate antitumor properties of metallic and nonmetallic nanomaterials to treat tumors, and related challenges and prospects are discussed. Keywords: tumor, nanomaterials, nanoparticles, nanotechnology